2015
DOI: 10.1186/s12284-014-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Forward screening for seedling tolerance to Fe toxicity reveals a polymorphic mutation in ferric chelate reductase in rice

Abstract: BackgroundRice contains the lowest grain Fe content among cereals. One biological limiting factor is the tolerance of rice to Fe toxicity. Reverse and forward genetic screenings were used to identify tolerance to Fe toxicity in 4,500 M4 lines irradiated by fast neutrons (FN).FindingsFe-tolerant mutants were successfully isolated. In the forward screen, we selected five highly tolerant and four highly intolerant mutants based on the response of seedlings to 300 ppm Fe. Reverse screening based on the polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…Higher Fe and Zn concentrations in the grains are desirable for human health. Ruengphayak found that the MuFRO1 mutant which tolerated Fe toxicity in the vegetative stage had 21–30% more grain Fe content than its wild type [ 47 ]. Therefore, breeding resistant rice varieties that tolerate high Fe and Zn concentrations with high content in the grains is an effective way to avoid soil pollution effects on agriculture [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher Fe and Zn concentrations in the grains are desirable for human health. Ruengphayak found that the MuFRO1 mutant which tolerated Fe toxicity in the vegetative stage had 21–30% more grain Fe content than its wild type [ 47 ]. Therefore, breeding resistant rice varieties that tolerate high Fe and Zn concentrations with high content in the grains is an effective way to avoid soil pollution effects on agriculture [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported QTL for tolerance to a variety of metal. With regards to Fe toxicity in rice, a total of 197 QTL have been reported (Wu et al, 1997 , 1998 , 2014 ; Wan J. L. et al, 2003a ; Wan J. M. et al, 2003b ; Wan et al, 2005 ; Shimizu et al, 2005 ; Ouyang et al, 2007 ; Dufey et al, 2009 , 2012 , 2015 ; Fukuda et al, 2012 ; Zhang et al, 2013 ; Zhao et al, 2013 ; Matthus et al, 2015 ; Ruengphayak et al, 2015 ; Liu et al, 2016 ). A total of four chromosomal regions (CR), including CR1 on chromosome 1 between markers RM246 and RM443; CR2 on chromosome 2 between markers RM526 and R758; CR3 on chromosome 3 between markers C515 and C25; and CR4 on chromosome 7 between markers R1245 and RM429, have been found to be involved in the resistance of rice to Fe toxicity (Dufey et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The functional prediction and database searching also suggested that OsFRO1 involvement in iron homeostasis [ 33 ] and the expression have been reported in leaves of Zn 2− , Mn 2− - and Cu 2− -deficient plants [ 48 ]. The expression of OsFRO1 gene was significantly correlated with Fe and/or Zn concentrations in seeds [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In rice only two ‘FRO-like’ genes ( OsFRO1 and OsFRO7 ) were identified, having unique functional characteristics in Fe uptake and abiotic stresses [ 16 , 32 ]. The expression of OsFRO1 was noticed in Zn 2− -, Mn 2− - and Cu 2− -deficient rice leaves and later their role in iron homeostasis and bulky biomass under Fe toxic condition was confirmed by [ 33 ], The rice OsFRO1 mutant showed more Fe content in grain when grown in iron-toxic soil [ 33 ]. Likewise, the knockdown of LeFRO1 transgene showed its effect on Fe partition in Nicotiana benthamiana [ 26 ].…”
Section: Introductionmentioning
confidence: 96%